2001
DOI: 10.1083/jcb.152.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Movement in Mitosis Requires Microtubule Anchorage at Spindle Poles

Abstract: Anchorage of microtubule minus ends at spindle poles has been proposed to bear the load of poleward forces exerted by kinetochore-associated motors so that chromosomes move toward the poles rather than the poles toward the chromosomes. To test this hypothesis, we monitored chromosome movement during mitosis after perturbation of nuclear mitotic apparatus protein (NuMA) and the human homologue of the KIN C motor family (HSET), two noncentrosomal proteins involved in spindle pole organization in animal cells. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 79 publications
(101 reference statements)
7
136
0
Order By: Relevance
“…Studies on HeLa cells disagree as to whether depleting CENP-E from kinetochores causes spindle fragmentation Yao et al, 2000). To resolve these differences, we examined CF-PAC cells, a human cell line that stays flat during mitosis (Gordon et al, 2001). As seen in Figure 5, a significant number of anti-CENP-E-injected CF-PAC cells exhibited multiple spindle poles with chromosomes aligned to the "minor" spindle poles ( Figure 5, b-d, yellow arrows).…”
Section: Spindle Morphology and Position Of Monooriented Chromosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on HeLa cells disagree as to whether depleting CENP-E from kinetochores causes spindle fragmentation Yao et al, 2000). To resolve these differences, we examined CF-PAC cells, a human cell line that stays flat during mitosis (Gordon et al, 2001). As seen in Figure 5, a significant number of anti-CENP-E-injected CF-PAC cells exhibited multiple spindle poles with chromosomes aligned to the "minor" spindle poles ( Figure 5, b-d, yellow arrows).…”
Section: Spindle Morphology and Position Of Monooriented Chromosomesmentioning
confidence: 99%
“…Furthermore, neither the injected antibodies nor an antibody directed against a different CENP-E epitope (Figures 1, c and f, and 6, b and c) detected CENP-E at the kinetochore. Moreover, depletion of CENP-E from kinetochores via antibody injection has functional consequences on aligned chromosomes as exemplified by an 87% drop in Mt-induced stretching between sister kinetochores (Table 2), with remaining tension apparently contributed by other proteins (Gordon et al, 2001). Finally, the mixed phenotype of both congressed and uncongressed chromosomes is found regardless of whether CENP-E disruption is accomplished via antibody injection, transfection of mutants , antisense RNA (Yao et al, 2000), or complete gene disruption in primary cells from mice (Putkey et al, 2000; data reported at the 40th annual meeting of the American Society for Cell Biology).…”
Section: Cenp-e Is Not Required For Congression Fast Poleward Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect immunofluorescence microscopy was performed as described previously (Gordon et al, 2001;Levesque and Compton, 2001). Fluorescent images were captured with a Hamamatsu Orca II cooled charge-coupled device camera mounted on an Axioplan 2 microscope (Carl Zeiss, Thornwood, NY) equipped for epifluorescence.…”
Section: Antibody Microinjection and Indirect Immunofluorescence Micrmentioning
confidence: 99%
“…Methods for time-lapse videomicroscopy and chromosome velocity measurements were described previously (Gordon et al, 2001;Levesque and Compton, 2001). Chromosome velocities were obtained from the digital time-lapse record of each cell.…”
Section: Time-lapse Microscopymentioning
confidence: 99%